מטכניקה לתודעה: על התפתחות הכתיבה האזוטרית בהגות היהודית במאה השתיים עשרה - שורץ דב (מחשבת ישראל, 2020)
During the twelfth century, Jewish thinkers began using an esoteric technique in their writing, concealing their views under a textual cover. In fact, they created two meanings for the text: one overt and one covert. The article argues that they did so unreflectively at first, without signs of awareness. A consciousness of esoteric writing took shape during the twelfth century and the article shows how, with this growing awareness, concealment techniques became richer. Should a theological or philosophical text written within a religious context necessarily be consistent? Should it be free of contradictions? Certainly not, and especially when it deals with issues the thinker considers abstract, loaded, touching on the most delicate questions of true faith and transcending easily understandable matters. The contradictions of authors who have produced outstanding works may be assumed to be deliberate rather than due to negligence since, from these writers’ perspective, they are directly concerned with immortality or, God forbid, with annihilation and disappearance. These are issues that determine whether humans will reach communion with God or be rejected and estranged. Tensions and sensitivities prevalent in the religious world only further ambiguous writing. In this article, I examine strains and inconsistencies deliberately used by considering several techniques of inconsistencies and intentional contradictions in twelfth-century Jewish thought, particularly in the writings of Judah Halevi and Maimonides. I intend to show how esoteric writing moved from the reality of a work based on contradictions to one that explicitly details its own contradictory nature. In other words, I want to show how esoteric writing shifted from practice to consciousness. I will first remark briefly on the characteristics of esoteric writing in the Middle Ages.